2022
DOI: 10.1111/mbe.12319
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Design and Children's Attention Allocation: Beyond the Laboratory and into the Classroom

Abstract: Prior laboratory research suggests the visual environment can be a source of distraction for children, reducing attention to instructional tasks and learning outcomes. However, systematic research examining how the visual environment relates to attention in genuine classrooms is rare. In addition, it is unknown what specific aspects of the environment pose a challenge for attention regulation. This observational study aims to (1) provide a nuanced examination of specific elements of the classroom visual enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…We did not measure children's environments during learning (e.g., presence of others, presence of distractors, etc.). While we can only speculate about the role of the learning environment on learning outcomes, it is important to acknowledge that presence of distractors and even visual complexity impairs learning in classroom environments (Fisher et al, 2014;Godwin et al, 2022) and book reading contexts (Eng et al, 2020). Future research should directly measure the impact on room environmental complexity and distraction on category learning in children in online environments.…”
Section: Limitationsmentioning
confidence: 99%
“…We did not measure children's environments during learning (e.g., presence of others, presence of distractors, etc.). While we can only speculate about the role of the learning environment on learning outcomes, it is important to acknowledge that presence of distractors and even visual complexity impairs learning in classroom environments (Fisher et al, 2014;Godwin et al, 2022) and book reading contexts (Eng et al, 2020). Future research should directly measure the impact on room environmental complexity and distraction on category learning in children in online environments.…”
Section: Limitationsmentioning
confidence: 99%
“…Exogenously regulated attention is largely an automatic process evident early in development; in contrast, endogenously regulated attention is thought to emerge later in development (e.g., Diamond, 2006;Luna, 2009;Ruff & Rothbart, 2001). In formal instructional contexts, the ability to endogenously regulate attention may be crucial for learning (Erickson et al, 2015;Fisher et al, 2014) as children need to inhibit a variety of distractions commonly found in classroom environments that compete for attention including distractions from peers, the surrounding visual environment, as well as the propensity to engage in self-distractions (Godwin et al, 2016(Godwin et al, , 2022.…”
Section: Word Count 137/120-150mentioning
confidence: 99%
“…A busy room can overwhelm students. Godwin et al (2022) show that students have better retention and focus in rooms that are not busy.…”
Section: Learning Spacesmentioning
confidence: 99%